ACCOMPANION FOR TRADEMARK REGISTRATION IN THE NAME OF MIE MELETUP - Cindo Cindo; Yudi Kornelis (ConCEPt - Conference on Community Engagement Project, 2022)
Mie Meletup is a business that is engaged in the culinary field which is an MSME (micro, small and medium enterprise). The business was established in 2021. A business formed mainly in the culinary field has a fairly high competitiveness. Legal protection for a trademark is needed to provide legal protection for the brand from actions that can be detrimental. Trademark rights are exclusive rights owned by a business in the form of a symbol or logo that is a special feature of a trademark or service that has been registered with the Director General of Intellectual Property Rights and has been ratified. Legal protection regarding Mark rights is regulated in Law Number 15 of 2001 concerning Marks. Brand rights are exclusive rights granted to trademark registrants that have been registered and protected by the Director General of Intellectual Property Rights. The purpose of brand protection is to prevent plagiarism of the brand. Data collection in this Student creativity program activity is using primary and secondary data collection. The output design process in the implementation of this Student creativity program activity begins with observations made to obtain location information, partner data, and problems that are being experienced by partners.